Early modern medievalisms : the interplay between scholarly reflection and artistic production - Montoya, Alicia; Romburgh, Sophia Georgina van, 1969-; Anrooij, W. van (Intersections (Boston, Mass.), 2010)
Modernity has historically defined itself by relation to classical antiquity on the one hand, and the medieval on the other. While early modernity's relation to Antiquity has been amply documented, its relation to the medieval has been less studied. This volume seeks to address this omission by presenting some preliminary explorations of this field. In seventeen essays ranging from the Italian Renaissance to Enlightenment France, it focuses on three main themes: continuities and discontinuities between the medieval and early modern, early modern re-uses of medieval matter, and conceptualizatio.